PENGEMBANGAN PROFESIONALISME GURU MELALUI PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN BERPOTENSI HKI BAGI GURU-GURU BAHASA ARAB MADRASAH ALIYAH SE KABUPATEN TULUNGAGUNG - Dariyadi, Moch Wahib; Huda, Ibnu Samsul; Ma'sum, Ali; Fauzan, Moh. (Universitas Negeri Malang, 2023)
This Community Service activity aims to enhance the understanding and knowledge of madrasah teachers regarding the importance of instructional media in the teaching process at the Madrasah. Additionally, the program trains teachers from Madrasah Aliyah in Kabupaten Tulung Agung to design and create interactive learning videos using the Camtasia Studio application. The specific objective of this training is to boost the creativity of teachers in designing and utilizing video-based learning media to make Arabic language teaching in the Madrasah more contextual. The methods employed in implementing this Community Service consist of lectures, training sessions, and Q&A sessions. The target audience for this activity includes teachers from Madrasah Tsanawaiyah and Madrasah Aliyah in Kabupaten Tulung Agung. This initiative effectively enhances teachers' knowledge regarding the urgency of instructional media and the development of various forms of instructional media, particularly related to technological advancements. Moreover, it improves teachers' skills in operating computers or laptops, particularly in integrating interactive media using Camtasia Studio. Following the training, there will be a two-month mentoring process and evaluation. The expected outcomes of this activity are (1) Proceedings of a National Seminar, (2) a community service journal article, and (3) an Intellectual Property Rights (IPR) for a Video Tutorial on Using Camtasia. Keywords: Media, Learning with Video, Camtasia Studio